Christology From the Perspective of a Batak Woman In Dalihan Natolu's Concept - Herowati Sitorus (LPPM IAKN Tarutung, 2021)
This research made the title Christology From the Point of View of Batak's Women In The Concept of Dalihan Natolu. The purpose of this research is to see how Batak’s women, in their patrilineal culture, have begun to clearly express their own christologies now. The women's emancipation movement has spurred the enthusiasm and courage of Batak's women to be more courageous in believing in Jesus Christ as Lord and Savior. The Dalihan Natolu's concept appreciates the existence of Batak's women as boru (daughters) who are ready to serve hula-hula (fathers, brothers or relatives of the wife's clan) as Jesus Christ be the Servant of God who serves. Writing this journal uses a case study qualitative research method by examining a particular case or phenomenon in society which is carried out in depth to study the background, circumstances, and interactions that occur. This research materials is taken from the textbooks, journals and other written materials. The research finding is that the events of the death and resurrection of Jesus Christ have made Batak's women aware of a human life, about a common desire to get liberation from any form. The findings in the study encourage Batak's women to emancipate in reflecting on the concept of dalihan natolu in their experience of understanding Christ.